Melissus, Time and Eternity - Pulpito, Massimo (Peitho. Examina Antiqua, 2017)
The traditional interpretation of Eleatism has it (1) that Melissus was a disciple of Parmenides (albeit with some divergences) and (2) that Parmenides believed in the timeless eternity of Being. It seems, on the contrary, (3) that Melissus acknowledged the reality of time by conceiving eternity as infinite time. Failing to justify this particular divergence from Parmenides’ approach, certain authors held that it was necessary to reinterpret the Melissan eternity as a form of infinite timelessness. This paper attempts to demonstrate that this reading is groundless and that if the traditional interpretation is questioned then one should reconsider the assumptions (1) and (2) but not (3).